2021
DOI: 10.1007/s00216-021-03248-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a method for the simultaneous analysis of fatty acid ethyl esters, ethyl sulfate and ethyl glucuronide in neonatal meconium: application in two cases of alcohol consumption during pregnancy

Abstract: Alcohol consumption during pregnancy constitutes one of the leading preventable causes of birth defects and neurodevelopmental disorders in the exposed children. Fatty acid ethyl esters (FAEEs), ethyl glucuronide (EtG) and ethyl sulfate (EtS) have been studied as potential biomarkers of alcohol consumption. However, most analytical approaches proposed for their analysis in meconium samples consist of separated extraction procedures requiring the use of two meconium aliquots, which is costly in terms of both ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…78 Although the used PubMed search term did not reveal any publication using meconium as sample matrix, several articles using GC-MS or LC-MS analysis are available. [79][80][81][82] MS-based bioanalytical procedures may allow direct and objective assessment of patient adherence, 5 and it has been demonstrated that MS-based monitoring improves adherence in nonadherent patients, 21,22 although access to specialized laboratory equipment and trained staff is required. Such analyses are cost intensive because the expenses for acquisition, operation, consumables, and personnel must be covered.…”
Section: Gap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…78 Although the used PubMed search term did not reveal any publication using meconium as sample matrix, several articles using GC-MS or LC-MS analysis are available. [79][80][81][82] MS-based bioanalytical procedures may allow direct and objective assessment of patient adherence, 5 and it has been demonstrated that MS-based monitoring improves adherence in nonadherent patients, 21,22 although access to specialized laboratory equipment and trained staff is required. Such analyses are cost intensive because the expenses for acquisition, operation, consumables, and personnel must be covered.…”
Section: Gap Analysismentioning
confidence: 99%
“…78 Although the used PubMed search term did not reveal any publication using meconium as sample matrix, several articles using GC-MS or LC-MS analysis are available. 79–82…”
Section: Gap Analysismentioning
confidence: 99%
“…Therefore, the volume of ethanol distribution is lower during dehydration and in women or the elderly due to lower muscle mass [18]. A minor fraction of ingested ethanol undergoes biotransformation prior to urinary excretion via glucuronidation to form ethyl glucuronide EtG (0.6-1.5%) or via sulfation to form ethyl sulfate EtS (0.1%) [19,21]. Both glucuronidation and the sulfation of ethanol are possible in the lungs and liver, and the median time to appearance of ethyl glucuronide and ethyl sulfate is approximately 20 h [22].…”
Section: Alcohol Intakementioning
confidence: 99%
“…Further studies are necessary to understand the differences in their pharmaco-toxicological profiles (4,(6)(7)(8). However, despite the health risks associated with their consumption, SCs have gained great popularity and several intoxications and fatalities related to halogenated SCs have been recently reported (1,6,(9)(10)(11)(12)(13)(14)(15). Particularly, many cases involved 4-CMC consumption along with other NPSs.…”
Section: Introductionmentioning
confidence: 99%